Effect of disturbed frequency on rock failure and energy characteristics exposed to triaxial fatigue and multistage unloading confining pressure (TF-MSUCP) conditions. (March 2023) - Wang, Yu; Tang, Pufeng; Li, Peng; Xia, Yingjie
Highlights: Alternative cyclic loading and unloading tests were performed to investigate rock fracture and energy characteristics. A low loading frequency is likely to induce greater radial deformation and complex crack network. Energy dissipation rate at the UCPS is larger than at the CLS, and it was described as function of confining pressure. Rock failure changes from mixed tensile-shear mode to pure shear mode with increasing disturbed frequency. Abstract: Rock is always encountered with disturbed stress, the respective excavation unloading and fatigue loading induced rock failure have been widely studied, yet the alternative fatigue loading and unloading on rock failure were not well understood. Herein, a series of triaxial fatigue and multistage unloading confining pressure (TF-MSUCP) tests were performed on granodiorite specimens with different disturbed frequency (i. e., 0.05, 0.1, 0.2, and 1.0 Hz). The stress strain responses, deformation, strain energy evolution, damage propagation, and mesoscopic failure pattern were investigated systematically. Testing results show that rock volumetric deformation, fatigue lifetime, dissipated energy, damage accumulation, and the failure modes were all influenced by the disturbed frequency (DF). The radial strain contributed greatly to the volumetric strain in the unloading confining pressure stage (UCPS) compared to the cyclic loading stage (CLS). The dissipated energy and failure pattern suggest that low disturbed frequency is prone to induce severe failure, in terms of greater radial deformation and complicated crack network. The relationship between the dissipated energy rate and confining pressure was established, and it is found that the dissipated energy rate is larger at UCPS than at CLS. A dissipated energy based damage evolution model was established, the model reveals the influence of disturbed frequency on damage accumulation. Post-test CT images revealed that the failure mode changes from mixed tensile-shear failure to pure shear failure with the increase of disturbed frequency.